Building thalamic neuronal networks during mouse development - Huerga-Gómez, Irene; Martini, Francisco J.; López-Bendito, Guillermina (Frontiers in Neural Circuits, 2023)
The thalamic nuclear complex contains excitatory projection neurons and inhibitory local neurons, the two cell types driving the main circuits in sensory nuclei. While excitatory neurons are born from progenitors that reside in the proliferative zone of the developing thalamus, inhibitory local neurons are born outside the thalamus and they migrate there during development. In addition to these cell types, which occupy most of the thalamus, there are two small thalamic regions where inhibitory neurons target extra-thalamic regions rather than neighboring neurons, the intergeniculate leaflet and the parahabenular nucleus. Like excitatory thalamic neurons, these inhibitory neurons are derived from progenitors residing in the developing thalamus. The assembly of these circuits follows fine-tuned genetic programs and it is coordinated by extrinsic factors that help the cells find their location, associate with thalamic partners, and establish connections with their corresponding extra-thalamic inputs and outputs. In this review, we bring together what is currently known about the development of the excitatory and inhibitory components of the thalamocortical sensory system, in particular focusing on the visual pathway and thalamic interneurons in mice.